A construção da memória e o metadiscurso em a resistência, de Julián Fuks. Uma abordagem semiótica - Miranda, Graciely Andrade (2019)
This research analyzes Julián Fuks's novel A resistência (2015), based on the theoretical instrumental of French semiotics. In the text we observe two inter-related narratives: the narrator's report of memories of past family life, marked by the adoption of a child during the Argentine military dictatorship and the report of the construction of the novel. Our aim is to understand both the way the protagonist narrator constructs his memories and the strategies he uses to simulate difficulties with the construction of the literary work he writes that has a metaficcional character and also analyses the construction of the narrator’s memory based on the two discursive forms of memory construction as an analytical category autobiographical discourses: a memory of past event and the event memory (BARROS, 2011). This study is based on a qualitative methodology of bibliographical revision about the author's work and French semiotic theory, conceived by Algirdas Julien Greimas and on the theoretical contributions of his successors, especially Denis Bertrand, for showing us the semiotic ways in the literature., Claude Zilberberg, who develops the concepts of event and field of presence, important for our work, and Mariana Luz Pessoa de Barros, who develops the concept of memory from the theoretical instrumental of tensive semiotics. The objective of our work is to analyze the narrator's memory construction based on the two discursive forms of memory construction as an analytical category of autobiographical discourses: the memory of the event and the memory-event (BARROS, 2011). This work is justified by analyzing a relevant contemporary novel in which recent historical events are recreated, through the narrator's social and individual memory, and it aims to contribute to the field of French semiotics, highlighting the way historical events affect the subjectivity of the narrator who recreates them in a work in which at the same time he reflects on the construction of the actor, as a character of literary fiction. In this sense, we will try to describe the thematic-figurative paths associated with literary metadiscourse.